2021
DOI: 10.1108/ijrdm-09-2020-0361
|View full text |Cite
|
Sign up to set email alerts
|

Designing a memorable in-store customer shopping experience: practical evidence from sports equipment retailers

Abstract: PurposeThis study aims to detect the dimensions of the in-store customer shopping experience from the sports retailer perspective and to investigate how the role of sports equipment stores is changing.Design/methodology/approachThis exploratory study performs semi-structured interviews with retail managers of sports equipment stores.FindingsThis research reveals the importance of the dimensions of immersive design, sensorial ambient elements, social relationships, trialability and real experience sharing in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…It uses PED as a cognitive behavioural therapy that potentially create specific feelings and examines its effects on all three dimensions. Previous studies on PED have suggested that design characteristics, such as PED, are used to positively evaluate design components, such as merchandise and ambience and digitalisation (Bonfanti and Yfantidou, 2021). Investments made through PED express that the retail, marketing strategies of a store are beneficial for developing consumer relationships (Arrigo, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It uses PED as a cognitive behavioural therapy that potentially create specific feelings and examines its effects on all three dimensions. Previous studies on PED have suggested that design characteristics, such as PED, are used to positively evaluate design components, such as merchandise and ambience and digitalisation (Bonfanti and Yfantidou, 2021). Investments made through PED express that the retail, marketing strategies of a store are beneficial for developing consumer relationships (Arrigo, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research has taken PED as a single construct; however, the future studies can take PED as a multi-dimensional construct (Bonfanti and Yfantidou, 2021) and then can examine the effect on EWB and its dimensions. This study has collected the data based on qualitative research.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, consumers find anything they are looking for online, and it is important to investigate why would the same consumers visit a brick-and-mortar shop (Smit, 2021). The effect of store atmosphere on consumer behavior has recently received much attention (Barros et al, 2019;Berčík et al, 2016;Bonfanti & Yfantidou, 2021;Helmefalk & Hultén, 2017). Berčík (2016) argued that consumers are first attracted to certain features within the store environment during the product selection stage, including lighting, music, scent, and color.…”
Section: Introductionmentioning
confidence: 99%
“…Touchpoints, especially those controlled by the organization, include but are not limited to the store environment and service personnel (employees) (De Keyser et al, 2020). These touchpoints are essential as they help create memorable customer experiences that become a competitive advantage and form of differentiation(Rather, 2020) in response to the threat of e-commerce(Bonfanti & Yfantidou, 2021).Numerous marketing literature has explored customer experience in the retail environment, starting with Holbrook and Hirschman (1982iors(Kazancoglu & Demir, 2021). As justified byZhu et al (2020), repeat purchase is based on the consumer's level of satisfaction with prior experiences.…”
mentioning
confidence: 99%